Підходи до оцінки зрілості бізнес-процесів підприємства з позиції їх економічної безпеки - Коптєва (Фадєєва), Ганна Миколаївна (My University, 2020)
У статті досліджено підходи до формування оцінки рівня зрілості бізнес-процесів підприємства на основі моделювання рівня їх зрілості. Обґрунтовано, що об’єктами управління й оцінки в сучасних умовах цифровізації є: бізнес-процеси підприємства, клієнтський досвід і сервіс, система цінностей, управління змінами та інноваціями, рівень конкурентоспроможності тощо. З точки зору автора, зрілість бізнес-процесів можна розглядати як критерій їх оцінки. А, оскільки, саме рівень зрілості бізнес-процесів прямим чином визначає їх здатність протистояти негативним зовнішнім і внутрішнім впливам (загрозам), то правомірно розглядати її критерій економічної безпеки бізнес-процесів підприємства. У результаті узагальнення моделей зрілості та врахування існуючих практик формування бізнес-процесів на підприємствах запропонована шестирівнева модель зрілості з урахуванням економічної безпеки бізнес-процесів: 1) найвищий рівень небезпеки; 2) початковий; 3) стандартний; 4) раціональний і формалізований; 5) контрольований і керований; 6) досконалий (найвищий рівень безпеки). Для оцінки рівня зрілості бізнес-процесів з позицій їх економічної безпеки розроблено низку показників, розрахунок яких і шкалювання значень дозволять ідентифікувати відповідний тип бізнес-процесів. Використання запропонованої моделі зрілості бізнес-процесів підприємства дозволять менеджменту підприємств адекватно застосовувати сучасні методи управління, засновані на процесному підході і сучасних інформаційних і комп'ютерних технологіях.

The article examines approaches to the formation of an assessment of the level of maturity of business processes of an enterprise based on maturity models. It is proved that the objects of management and evaluation in modern conditions of digitalization are: business processes and tools of the enterprise, customer experience and service, value system, change and innovation management, competition and competitiveness problems, and so on. Therefore, the maturity of business processes can be considered as a criterion for evaluating them. And, since the level of maturity of business processes is directly related to their economic security, it is possible to introduce a criterion for the economic security of business processes of the enterprise. As a result of generalization of maturity models and taking into account existing practices of business process formation at enterprises, the following levels of maturity were proposed, taking into account the economic security of business processes: 1 – the highest level of danger; 2 – initial; 3 – standard; 4 – rational and formalized; 5 – controlled and managed; 6 – perfect (the highest level of security). It is proposed to determine the level of economic security of business processes based on their maturity using indicators, the calculation of which and scaling values will identify the appropriate type of business processes. The definition and use of the maturity model in assessing the quality and effectiveness of the formation of business processes of the enterprise will allow the management of enterprises to adequately implement modern management methods based on the process approach and modern information and computer technologies. The use of the maturity model is a necessary condition for evaluating the effectiveness of business processes, since it is impossible to effectively operate any system, including economic security, at an enterprise with a low level of business process maturity. The developed model is based on a process approach to management, taking into account economic security. it can be used to obtain an adequate assessment of the level of economic security of the enterprise's business processes.
Approaches to assessing the maturity of enterprise business processes from the perspective of their economic security
Keywords: цифрова трансформація; економіка; інформаційні технології; управління; менеджмент підприємств; business process; maturity model; economic security criterion; digital transformation